PROGRAM RIAU TELEVISI DALAM MELESTARIKAN BUDAYA MELAYU (Studi Deskriptif Program Acara Berbual dalam Dendangan Riau Televisi) - Rini Anggriany; Nurjannah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Berbual dalam dendangan program is a talk show program which aims to provide knowledge and information to discuss about malay culture. This program is based on reality of society Riau who lack knowledge about the malay culture. The aim of this study was to determine how the material covered, the program strategy in attracting audiences and interests of the audience’s response.This study used qualitative method with descriptive approach. Data collection techniques used were based on the fact the field through observations, interviews, and documentation. Informants in this study amounted to 8 people are composed of the program manager, produser and host, two humanists and 4 people in the crowd were selected based on purposive sampling. As for the examination of the validity of the data the researchers used a technique of triangulation.These results showed that the material covered on the Riau Television program berbual dalam dendangan in preserving the culture of the malay namely the malay arts, customs and culinary wither. The material chosen according aspects of malay culture and overall depict malay culture. As well as strategies berbual dalam dendangan program to attract viewers. The strategy used consists of the selection time slot, the appropriate host, the guest speaker on topic, packaging, and outreach programs broadcast. The strategy is executed during the delivery period berbual dalam dendangan program to attract audiences. Audiences response about this program managed to attract viewers and provide new knowledge about the malay culture. Most of the audiences gave a positive response about the material and packaging the program then there is also a negative response on the consistency of views, setting and concept studio, variety of topics as well as creations when opening berbual dalam dendangan program.Keyword: program, culture, malay, talkshow, studies, descriptive